2015
DOI: 10.1007/s10943-015-0020-y
|View full text |Cite
|
Sign up to set email alerts
|

Missed Opportunity: Spirituality as a Bridge to Resilience in Latinos with Cancer

Abstract: Going through adverse life events can help a person learn how to cope with life’s challenges, overcome them, learn from the adverse experiences, grow, and be positively transformed by them. Spirituality is a resource that supports adaptation and resilience to improve quality of life in patients with cancer or other chronic illnesses. For Latinos, spirituality is an important core cultural value. As such, it is crucial to pay close attention to how cultural values play a role in health-related concerns when car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
50
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 61 publications
(55 citation statements)
references
References 48 publications
3
50
0
2
Order By: Relevance
“…However, in this investigation, there was no evidence to suggest that SES was associated with stress or distress. This may be a case of resilience in the Latina community whereby those who are seemingly disadvantaged by virtue of having low SES nevertheless find sources of strength and coping through such mechanisms as spirituality for example . A related finding in the literature showed that Latinas with low education who lived in high‐SES neighborhoods actually had a lower breast cancer mortality rate than do non‐Latina white women with high education in high‐SES neighborhoods .…”
Section: Discussionmentioning
confidence: 98%
“…However, in this investigation, there was no evidence to suggest that SES was associated with stress or distress. This may be a case of resilience in the Latina community whereby those who are seemingly disadvantaged by virtue of having low SES nevertheless find sources of strength and coping through such mechanisms as spirituality for example . A related finding in the literature showed that Latinas with low education who lived in high‐SES neighborhoods actually had a lower breast cancer mortality rate than do non‐Latina white women with high education in high‐SES neighborhoods .…”
Section: Discussionmentioning
confidence: 98%
“…Such responses primarily demonstrated participants' feelings of being blessed, turning their burden over to “the Lord,” feeling “closer to God,” offering and receiving prayer, and finding an existential meaning in their cancer experience and survival. The specific significance of spirituality is not a surprising finding as spirituality has long been identified as an important core cultural value among ethnic groups . Ample research based on samples comprising African American, Latino, and Asian cancer survivors demonstrates a major role of spirituality in survivors' ability to adjust to and cope with the physical, psychological, emotional, and social burdens associated with cancer .…”
Section: Discussionmentioning
confidence: 99%
“…The specific significance of spirituality is not a surprising finding as spirituality has long been identified as an important core cultural value among ethnic groups. [29][30][31] Ample research based on samples comprising African American, Latino, and Asian cancer survivors demonstrates a major role of spirituality in survivors' ability to adjust to and cope with the physical, psychological, emotional, and social burdens associated with cancer. 29,[31][32][33] Such research also reveals spirituality to be an important protective factor as survivors experience their individual and often circuitous trajectory of diagnosis, treatment, and transition from active treatment to longterm survivorship.…”
Section: Typology Domain Life Perspective-new Positive Philosophy Onmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings are consistent with previous studies that concluded Latinos endorse a greater interest in religious/spiritual counseling in the cancer context than their non-Latina White counterparts. (Yanez et al 2016, Yanez, Stanton, and Maly 2012, Hunter-Hernandez, Costas-Muniz, and Gany 2015, Jurkowski, Kurlanska, and Ramos 2010). It has been demonstrated that religion can promote the use of health services in Latino religious communities (Leyva et al 2014), and parishes have expressed their support to provide cancer care to their communities (Allen et al 2014).…”
Section: Discussionmentioning
confidence: 99%